Nipah virus strikes Kerala: recent cases and implications - Srivastava, Shriyansh; Sharma, Pramod Kumar; Gurjar, Saurav; Kumar, Sachin; Pandey, Yogesh; Rustagi, Sarvesh; Mohanty, Aroop; Sah, Ranjit (The Egyptian Journal of Internal Medicine, 2024)
The Nipah virus, a highly pathogenic zoonotic pathogen, has once again surfaced in the state of Kerala, India, with recent cases reported in 2023. This article delves into the epidemiological details of these cases, shedding light on the two fatalities that occurred in September 2023 and August 2023 as well as the suspected cases that have undergone testing. Nipah virus, known for its severe neurological and respiratory disease manifestations, remains a formidable health threat due to the lack of specific treatments or vaccines. The government’s response to these recent cases, including mass testing and quarantine measures, is discussed, drawing lessons from past outbreaks in the region. Kerala has experienced multiple Nipah virus outbreaks since 2018, prompting a closer examination of environmental factors, such as deforestation and urbanization, which increase the risk of zoonotic transmission. This article underscores the global implications of Nipah virus resurgence in Kerala and emphasizes the importance of preparedness and vigilance in the face of emerging infectious diseases. The lessons learned from Kerala’s experience with Nipah virus outbreaks provide valuable insights for public health professionals and policymakers worldwide.